Jugular venipuncture and other innovative approaches to phlebotomy among people who inject drugs. (26th August 2015) - Ferguson, Catherine; Higgs, Peter; Olsen, Anna
Abstract In their recent paper on patient experiences of accessing phlebotomy services in hospital outpatient clinics, Clements and colleagues state that there is a real need to better understand the responses of people who inject drugs to phlebotomy. They discuss the reasons why people who inject drugs might not be accessing healthcare services, especially in relation to treatment for hepatitis C. Their research is a welcome addition to the literature that emphasizes the stigma and discrimination faced by people who inject drugs, including within healthcare settings, and outlines the need to promote effective partnerships between healthcare workers and patients so as to deliver the best health outcomes.